DOI: 10.18297/etd/2862
|View full text |Cite
|
Sign up to set email alerts
|

Role of human arylamine n-acetyltransferase 1 in tumorigenesis and cancer biology.

Abstract: help of Dr. Mary Ann Sanders, in teaching me pathology classifications and helping classify the pathology slides. Thank you to Dr. Dennis Warner for instructing me on the isolation and culture of mouse embryonic fibroblasts. Thank you to Jamie Rush for being a helpful neighbor in the laboratory. Thank you to the summer students that I had the pleasure of instructing over the summers of my graduate studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 97 publications
(132 reference statements)
1
3
0
Order By: Relevance
“…Based on results of this study, our laboratory and others are utilizing CRISPR/Cas9 to make permanent deletions at the NAT1 gene open reading frame causing 100% knockout of NAT1. In preliminary studies, our laboratory has reported that NAT1 knockout in MDA‐MB‐231 breast cancer cell lines with two different guide RNAs replicates the results reported here with shRNA partial NAT1 knockdown . In summary, inhibition of NAT1 by either partial knockdown (shRNA) or small molecule inhibition reduced anchorage‐independent growth in the MDA‐MB‐231 human breast cancer cell line.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Based on results of this study, our laboratory and others are utilizing CRISPR/Cas9 to make permanent deletions at the NAT1 gene open reading frame causing 100% knockout of NAT1. In preliminary studies, our laboratory has reported that NAT1 knockout in MDA‐MB‐231 breast cancer cell lines with two different guide RNAs replicates the results reported here with shRNA partial NAT1 knockdown . In summary, inhibition of NAT1 by either partial knockdown (shRNA) or small molecule inhibition reduced anchorage‐independent growth in the MDA‐MB‐231 human breast cancer cell line.…”
Section: Discussionsupporting
confidence: 79%
“…Portions of this work constituted partial fulfillment of a PhD in Pharmacology and Toxicology at the University of Louisville for Marcus W. Stepp . This work was supported in part by the National Institute of Environmental Sciences [Grant USPHS T32‐ES011564].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Individual knockout cell lines representing the knockout of NAT1 activity for gRNA #2 or #5 were chosen based on NAT1 enzymatic activity and genomic sequence. Further details on NAT1 knockout cell line construction and characterization are described elsewhere [25].…”
Section: Methodsmentioning
confidence: 99%
“…The construction and characterization of the siRNA generated cell lines has been described extensively elsewhere 82,84,115,116 . Briefly, three cell lines were constructed, Scrambled,…”
Section: Construction Of Sirna Generated Cell Linesmentioning
confidence: 99%